IMPROVING SCIENCE LEARNING OUTCOMES THROUGH CORE LEARNING MODEL BASED ON SETS - Suci, Ni Komang Ayu Ari; Pudjawan, Ketut; Parmiti, Desak Putu (Jurnal Ilmiah Sekolah Dasar, 2020)
The low learning outcomes of science caused by the implementation of learning that has not been able to foster an atmosphere of active learning, fun and motivating students during learning, so that the impact on student learning outcomes is low science. This study aims to analyze the influence of the Connecting Organizing Reflecting Extending (CORE) -based Science Environment Technology Society (SETS) learning model on student science learning outcomes in elementary schools. This type of research is quasi-experimental (Quasi Experiment) with a research design that is Posttest Only Control Group Design. Science learning outcomes data obtained through the test method with data collection instruments in the form of multiple choice questions totaling 25 items. Data on learning outcomes that have been collected are then analyzed using descriptive statistics and inferential statistics. Based on the results of descriptive analysis, the average value of students in the experimental group was 76.00 and the average value of the control group students was 62.82. Based on the results of data analysis that has been done using the T-Test obtained tcount of 2.992 while ttable of 2,000. This means that the t-count is greater than the table, so H0 is rejected and H1 is accepted with the conclusion that there is an effect of the Learning Environment Connecting Reflecting Extending (CORE) model based on the Science Environment Technology Society (SETS) on the science learning outcomes of students in elementary school.